PELAKSANAAN STANDAR OPERASIONAL PROSEDUR PEMESANAN MAKANAN DI PRIME STEAK HOUSE FINE DINING RESTORAN JW MARRIOTT HOTEL MEDAN - Ivan Benedict Tambunan (Jurnal Ilmiah Akomodasi Agung, 2020)
Fine Dining is a restaurant-style dining concept that offers a luxurious atmosphere and classy service. Stages of serving food in Fine Dining restaurants start from Appetizer to Dessert. Visitors who come usually wear neat and formal clothes. Men wear shirts, suits and for women use Luxurious dresses and clothes. In serving guests so that guests are satisfied, it is necessary to implement standard operating procedures by waiters. The waiter should carry out the stages in serving guests who order food at Prime Steak House Fine Dining Restaurant JW Marriott Hotel Medan 'To get more accurate data, the writer conducted a direct observation of the object to be studied using this type of descriptive research by observing and interviewing 15 guests. This research was conducted for 6 (six) months, starting from August 2019 to February 2020.From the results of the author's analysis, it was found that the waitresses were still lacking in implementing standard operational procedures for ordering food at the Prime Steak Fine Dining Restaurant which resulted in guests being less satisfied while in the restaurant. The implementation of the food ordering procedure has been set at the Prime Steak House Fine Dining Restaurant, but there are still waiters who do not do their job properly and maximally, for example errors in recording food orders or taking orders, not offering dessert, and not informing guests of the time it takes for food to be received guest.